Establishing a lasting legacy : six steps to maximize your leadership impact and improve teacher retention - Evers-Gerdes, Becky; Siegle, Ryan (Solution Tree Press, 2021)
"In Establishing a Lasting Legacy: Six Steps to Maximize Your Leadership Impact and Improve Teacher Retention, authors Becky Evers-Gerdes and Ryan Siegle address the teacher retention problem and provide school leaders with strategies and tools for supporting and retaining great teachers. The authors share their research-based model for building personal, relational, and organizational capacity as well as for developing healthy and trusting school environments. The model asks leaders to understand themselves first before moving outward to build self-efficacy in those they lead. By engaging in this systematic process, readers grow their self-awareness and authenticity as leaders and provide needed support to staff"--